Educação escolar da pessoa com deficiência e/ou necessidades especiais na escola de tempo integral - Leite, Michele de Mendonça (2017)
This work is inserted in the research line Culture and Educational Processes, which integrates the Post-Graduate Program in Education of the Faculty of Education of University Federal of Goiás and had funding by the Goiás State Research Foundation – FAPEG. The purpose of this study was to understand the project of integral education (human education) for students with disabilities and/or special needs in full-time school, more precisely at the EMEI Monteiro Lobato, in the city of Aparecida de Goiânia - GO. In this sense, it sought to identify what legal and pedagogical policy frameworks, which guide work in full-time educational institutions affirm with respect to Special Education in an Inclusive perspective; It understands how school time has been organized for the performance of specialized educational services, since the activities of the Specialized Educational Assistance (AEE) and the curricular activities of the full-time school take place in the counter-shift, conceiving that it is a function Of the school to socialize the knowledge historically accumulated to all. To apprehend the meanings and meanings of teachers about being a teacher in full - time schools for the targeted public education students. When mapping, in the thesis bank of CAPES, we understand that there are few studies in the state of Goiás that address this theme, which indicated the need to broaden the discussions about the teaching - learning of these students in this context of the full - time school. Taking as a guideline the method in Marx, this investigation is configured as a bibliographical - documentary and field, whose procedure for data collection was the semistructured interview recorded in audio with teachers of EMEI Monteiro Lobato, in order to apprehend the senses and meanings Teachers' about these issues, as well as observation, which allowed us to capture in more detail the school context and its various connections. The analyzes of the data obtained were based on the theoretical - philosophical assumptions of Historical - Critical Pedagogy (SAVIANI, 2013) and Historical - Cultural Psychology (VYGOTSKI, 1997). The results obtained from this research revealed a assistance project to people with disabilities and / or special needs that overlaps the pedagogic. Due to the precarious working conditions, with professional training due to the negligence of the target audience of special education, reinforcing the phenomenon of excluding inclusion and/or alienated inclusion.